Phytoplasma Associated with White-backed Planthopper on Rice Plants in Sidrap Regency, South Sulawesi - Abbas, Saipul; Djaya, Ernawati; Najamuddin, Erwin; Sebayang, Amelia; Rahman, Ayyub Ar; Aminah, Aminah; Hasbi, Hasbi; Sipi, Surianto; Ridwan, Nur Fathurahman; Ismayanti, Rini; Ibrahim, Elisurya (Jurnal Perlindungan Tanaman Indonesia, 2024)
South Sulawesi is one of the largest rice production centers in Indonesia. Several important diseases of rice plants, such as those caused by viruses and phytoplasmas, can be transmitted by insect vectors, especially leafhoppers and stem plant. Symptoms of diseases caused by viruses and phytoplasmas are quite diverse but visually similar and difficult to distinguish. This study aims to analyze the presence of phytoplasma associated with white-backed planthopper which are commonly found in rice plantations.  The research method used is by conducting surveys and explorations of insect samples in six villages in Sidrap District. White-back planthoppers found on rice plantations showing symptoms of yellowing and stunted leaves were sampled for further analysis, including total DNA isolation of insects, standard PCR amplification for insect and Nested-PCR for phytoplasma identification, gene sequencing for both amplicons, and nucleotide analysis using BLAST method and Mega X program. The PCR with CO1 primer successfully amplified a 700 bp amplicon from insects, whereas nested-PCR using fP1/rP7 primers followed by m23SR/R16F2n amplified phytoplasma supposedly around 1800 bp and 1250 bp of 16S RNA gene, respectively. The DNA sequencing analysis results indicate that the insect samples were identified as 83% Sogatella vibix species based on homology percentage analysis using BLAST and Mega X Program. As for the phytoplasma, it leans more towards the 16SrI group or Candidatus phytoplasma asteris (Aster yellows phytoplasma) with a homology percentage of 99%.